The Effectiveness of the Discovery Learning Model Assisted by Video Games to Improve Student Learning Outcomes on the Concept of Momentum and Impulse in High School - Mohamad Nurkhojin; Abdul Haris Odja; Trisnawaty Junus Buhungo; Mursalin Mursalin; Ritin Uloli; Citron S Payu (Physics Education Research Journal, 2022)
This  study aims  to determine the   effectiveness of the   discovery learning   model with the   help of   video games on   student  learning  outcomes on the  concept of  momentum and  impulse  in    high  school.  This  research  is  using  an  experimental  method. The research  design  used  was  a pretest-posttest  control  group  design. In this  study there  was an experimental   group   and  a control  group. Data collection  using  essay test  and  multiple  choice  tests. Data  analysis using  the mean  difference  analysis  and  N-Gain. The results  showed  that the t-value on the multiple-choice test was   2.183 and on the  essay   test was 2.811, which was  greater  than t-table  2.037. Referring  to the rule  of  testing the  hypothesis  that  if tcount  ttable, then  H0  is rejected, H1 is  accepted, which  means  there  is  a significant  influence.  So  it  can  be  concluded  that learning   using the   discovery learning   model with  the  help  of  video games  has a significant  effect  on  student  learning outcomes   on  the  concept  of  momentum and  impulse  in high  school.  Through the n-gain test   on the   multiple  choice  test  it  can  be  seen  that the N-gain value  for   the   experimental  class  is  0.713 and the control   class  is  0.582.  While  on the   essay   test for the   experimental   class   0.777 and  0.667 for the  control  class. So it  can  be  concluded  that the increase  in student learning   outcomes  using the discovery   learning  model with the   help of video games  is  higher  than the use  of the discovery learning  model on  the  concept  of  momentum and  impulse  in high  school.